2020
DOI: 10.1002/ente.202000424
|View full text |Cite
|
Sign up to set email alerts
|

Improving Grain Boundary Conductivity of Ce0.9Gd0.1O2 − δ Electrolyte through Compositing with Carbonate or Semiconductor

Abstract: In the solid oxide fuel cell field, heterogeneous ion doping is a common methodology to improve the ionic conductivity of electrolytes, but overwhelming grain boundary resistance is still the main obstacle for low‐temperature applications. According to previous reports, building rapid ion transport at the grain boundary through compositing methods was considered as a proposed design for electrolytes to decrease the grain boundary resistance and obtain high ionic conductivity. Herein, Ce0.9Gd0.1O2 − δ (GDC) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…Furthermore, the morphology of NCAL reveals the fluffy and well-porous structure assists in mass transfer with the extension of the triple-phase boundary depicted in Figure 7 C. At the same time, GDC-Na 2 CO 3 seems too dense without pores after sintering at 575 C, and the desired density assists in separating the H 2 and air gases or prevents the contact between air and H 2, as illustrated in Figure 7 D. The XRD of GDC and GDC-Na 2 CO 3 reveal a pure fluorite structure. Still, with the addition of Na 2 CO 3, the peak intensity is lower, and slight expansion is noticed, confirming the formation of a GDC-Na 2 CO 3 structure without impurity peaks, as demonstrated in Figure 7 E. 22 , 67 During the fuel cell operation, it is known that Na 2 CO 3 changes into a molten state and makes connections or bonds with other materials, as seen in the examples with SDC-Na 2 CO 3 , GDC-Na 2 CO 3, etc., to attain nanocomposite material characteristics. 67 The relationship between the functions of the different particles as quick ions transport channels simultaneously speeds up the process leading to enhanced electrochemical fuel cell performance with a power density of 800 mW/cm 2 at 575 C shown in Figure 7 F. Moreover, several studies have been reported to enhance the ionic conduction and boost the fuel cell performance using the above stated phenomena.…”
Section: Ceria-based Composites and Nanocomposites As Alternative Ele...supporting
confidence: 60%
See 4 more Smart Citations
“…Furthermore, the morphology of NCAL reveals the fluffy and well-porous structure assists in mass transfer with the extension of the triple-phase boundary depicted in Figure 7 C. At the same time, GDC-Na 2 CO 3 seems too dense without pores after sintering at 575 C, and the desired density assists in separating the H 2 and air gases or prevents the contact between air and H 2, as illustrated in Figure 7 D. The XRD of GDC and GDC-Na 2 CO 3 reveal a pure fluorite structure. Still, with the addition of Na 2 CO 3, the peak intensity is lower, and slight expansion is noticed, confirming the formation of a GDC-Na 2 CO 3 structure without impurity peaks, as demonstrated in Figure 7 E. 22 , 67 During the fuel cell operation, it is known that Na 2 CO 3 changes into a molten state and makes connections or bonds with other materials, as seen in the examples with SDC-Na 2 CO 3 , GDC-Na 2 CO 3, etc., to attain nanocomposite material characteristics. 67 The relationship between the functions of the different particles as quick ions transport channels simultaneously speeds up the process leading to enhanced electrochemical fuel cell performance with a power density of 800 mW/cm 2 at 575 C shown in Figure 7 F. Moreover, several studies have been reported to enhance the ionic conduction and boost the fuel cell performance using the above stated phenomena.…”
Section: Ceria-based Composites and Nanocomposites As Alternative Ele...supporting
confidence: 60%
“…Still, with the addition of Na 2 CO 3, the peak intensity is lower, and slight expansion is noticed, confirming the formation of a GDC-Na 2 CO 3 structure without impurity peaks, as demonstrated in Figure 7 E. 22 , 67 During the fuel cell operation, it is known that Na 2 CO 3 changes into a molten state and makes connections or bonds with other materials, as seen in the examples with SDC-Na 2 CO 3 , GDC-Na 2 CO 3, etc., to attain nanocomposite material characteristics. 67 The relationship between the functions of the different particles as quick ions transport channels simultaneously speeds up the process leading to enhanced electrochemical fuel cell performance with a power density of 800 mW/cm 2 at 575 C shown in Figure 7 F. Moreover, several studies have been reported to enhance the ionic conduction and boost the fuel cell performance using the above stated phenomena. 37 , 45 , 62 , 67 , 68 , 69
Figure 7 Conduction path for protons and ions along with morphology, stuctural and electrochemical properties of GDC/NCO (A and B) Schematic diagram of fuel cell device with GDC-Na 2 CO 3 electrolyte and NCAL electrode along with the conduction path of protons and oxide ions, (C and D) SEM image of NCAL porous electrode and electrolyte membrane GDC-Na 2 CO 3 , (E and F) XRD analysis of GDC, GDC-Na 2 CO 3, and performance of GDC-Na 2 CO 3 electrolyte membrane 67 with permission of John Wiley and Sons.
…”
Section: Ceria-based Composites and Nanocomposites As Alternative Ele...supporting
confidence: 60%
See 3 more Smart Citations